The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4062/biomolther.2012.072
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effects of Lycii Radicis Cortex and Betaine in the Forced Swimming Test in Rats

Abstract: The purpose of the present study was to examine the effect of Lycii Radicis Cortex (LRC) and betaine (BT) on immobility and neurochemical change in the forced swimming test (FST) in the rat. LRC, BT or fluoxentine was administered intraperitoneally to Sprague-Dawley rats three times (1, 5 and 23.5 h) before the FST. To investigate antidepressant-like effect, serotonin (5-HT) and norepinephrine (NE) were examined in the hippocampus and hypothalamus of rats. LRC (100 mg/kg) and BT (30, 100 mg/kg) significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…On the other hand, D-serine (Malkesman et al 2012) and glycine transporter-I inhibitor sarcosine (Chen et al 2015;Huang et al 2013), which are assumed to potentiate NMDAR function through glycine site, can also improve depression-like behaviors in rodent models and in human depression (Huang et al 2013). Modulation of NMDAR glycine site might be majorly contributed to the rapid and sustained antidepressant-like effect of betaine, although betaine elevated 5-HT levels and has been suggested to be like a traditional antidepressant (Kim et al 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, D-serine (Malkesman et al 2012) and glycine transporter-I inhibitor sarcosine (Chen et al 2015;Huang et al 2013), which are assumed to potentiate NMDAR function through glycine site, can also improve depression-like behaviors in rodent models and in human depression (Huang et al 2013). Modulation of NMDAR glycine site might be majorly contributed to the rapid and sustained antidepressant-like effect of betaine, although betaine elevated 5-HT levels and has been suggested to be like a traditional antidepressant (Kim et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Based on the structural similarity to glycine, we have examined if betaine can affect the NMDAR function and demonstrated that betaine acts like a NMDAR glycine binding site partial agonist (Lee and Chen 2014). Furthermore, betaine exhibits antidepressant-like effects in rats (Kim et al 2013). Accordingly, it is hypothesized that betaine can promote the antidepressant-like but antagonize the psychotomimetic effect of ketamine.…”
Section: Introductionmentioning
confidence: 99%
“…. 또한 지골피 성분으로는 cinnamic aldehyde와 다량 의 phenol, betaine, alkaloid, kukoamine 등이 알려져 있 으며 10) , 실험연구로 항우울증 11) , 항산화 12) , 간 보호 10,14) . 산수유의 주성분은 triterpene 계 열인 saponin, ursolic acid, stearic acid, linolenic acid, palmitic acid, oleic acid, morroniside, loganin, valine, tyrosine 등이 알려져 있으며 15) , 생리활성으로 항알러지 16) , 간 보호 17) , 항당뇨 18) , 항염증 19 …”
Section: 서 론 1)unclassified
“…In addition, LRC inhibits hepatic damage induced by CC14 (Cho and Kim ) and depressed state (Kim et al . ) in mice. Furthermore, tyramine derivatives or phenolic amides from LRC exhibit hypocholesterolemic, antioxidative or anti‐inflammatory effects (Cho et al .…”
Section: Introductionmentioning
confidence: 97%